Historical Legends of the Volga-Ural Muslims concerning Alexander the Great, the City of Yelabuga, and Bāchmān Khān - Allen J. Frank (Revue des Mondes Musulmans et de la Méditerranée)
Since the beginning of the 19th century the written traditions of the Volga-Ural Muslims have recorded a cycle of historic and genealogical legends involving Iskandar Dhū 1-Qarnayn (Alexander the Great) and the city of Yelabuga, located on the Kama River, today within the Russian Federation's Republic of Tatarstan. This paper will attempt to identify and trace the variants of these legends, to a large degree found in the region's Islamic manuscript collections, and to determine what role they played in the development of a communal identity among Volga-Ural Muslims.The traveler Abū Hamid al-Ghamāti (12th century) mentions that the Volga Bulgarians considered themselves descended from Alexander. These legends appear to have their complex origins in the traditions of certain Muslim steppe nomads and pre-Mongol Volga Bulgarians. A number of genealogies, especially those of the Chepets Tatars in northern Udmurtia, trace their origins to one Sōqrāt Hakim (Socrates), who reportedly came to the Noghay lands ; and to a degree these traditions appear to have become intertwined. Enigmatic too are the legends concerning the city of Yelabuga, which is said to have been founded by Alexander and his companion, Sōqrāt Hakim. Yelabuga is depicted both as the sacred location of numerous Muslim saints' tombs, and as a center of unbelief, ruled by infidel rulers - particularly, a certain Bāchmān Khān who appears to be connected with a historical figure of the same name and who is mentioned in Tatar tradition as the son of Sōqrāt Hakim.